The anesthetic management of a patient with dorfman-chanarin syndrome - Beştaş, Azize; Bolat, Esef; Bayar, Mustafa K.; Erhan, Ömer L. (My University, 2011)
Dorfman-Chanarin syndrome (DCS), which is also known as neutral lipid storage disease, is a rare autosomal recessive inherited lipid storage disease with congenital ichthyotic erythroderma. Since the Dorfman-Chanarin syndrome is a multisystemic disease the choice of drugs and the conduct of anesthesia in these patients are important. Preoperative evaluation should be performed in detail and anesthetic method and drugs to be used should be chosen carefully in accordance with affected system, overall state of patient and characteristics of the operation, in order to decrease perioperative morbidity rates in these patients. We report the anesthetic management of a child with DCS operated for correction of strabismus under general anesthesia.
Keywords: Anesthesia; Dorfman-chanarin syndrome